Adjuvant endocrine therapy in breast cancer - Niwińska, Anna; Litwiniuk, Maria (Contemporary Oncology/Współczesna Onkologia, 2007)
Endocrine therapy is the most important component of adjuvant therapy for patients with hormone receptor-positive breast cancer, regardless of age and menopausal status. Tamoxifen improves survival in premenopausal and postmenopausal women. In premenopausal patients it is used alone, in combination with ovarian suppression, or sequentially, after chemotherapy. Ovarian ablation/suppression in the absence of chemotherapy significantly improves survival in patients younger than 50. Combined with tamoxifen it offers an outcome similar to that of CMF chemotherapy. There is no clear benefit from adding ovarian ablation/suppression after chemotherapy. Aromatase inhibitors are now considered an integral part of endocrine therapy in postmenopausal women. They can be given as initial adjuvant treatment, sequentially with tamoxifen or as extended therapy after tamoxifen. However, neither the optimal duration nor sequencing nor long-term safety of aromatase inhibitors is known. They should not be given in premenopausal women otherwise than in clinical trials.